SPIRITUALITAS DI ERA MODERN DALAM TAFSIR KONTEMPORER TELA’AH TERHADAP TAFSIR AL-MUNIR DAN TAFSIR AL-AZHAR DALAM SURAT ADZ-DZARIYAT AYAT 56 - Qoriy, Moh Silvan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research discusses the understanding of spirituality in the modern era through an examination of Tafsir al-Munir by Wahbah al-Zuhaili and Tafsir al-Azhar by Buya Hamka, with a focus on the interpretation of QS. Adz-Dzariyat verse 56. The research method employed is qualitative with a library research approach, which involves analyzing primary sources such as Tafsir al-Munir and Tafsir al-Azhar, as well as secondary sources including journals, articles, and relevant academic literature. The findings reveal that both Wahbah al-Zuhaili and Buya Hamka agree that the primary purpose of the creation of humankind and jinn is to serve and worship Allah SWT. Both emphasize that spirituality is not limited to formal ritual worship but also encompasses all aspects of life founded upon sincerity. Wahbah al-Zuhaili places greater emphasis on the dimensions of ma’rifatullah (knowledge of God), tazkiyatun nafs (purification of the soul), and the role of spirituality as a guide in confronting the temptations of modern materialism. Meanwhile, Buya Hamka, through his concept of Modern Sufism, highlights the importance of inner reflection, self-restraint, and moral cultivation as solutions to the spiritual emptiness experienced by contemporary society.